Developing a nutritious soup product using purple sweet potatoes supplemented with composite of vegetables and freezed-dried chicken - Nguyen Minh THUY; Tran Ngoc GIAU; Vo Quoc TIEN; Nguyen Van THANH; Ngo Van TAI (My University, 2023)
This research aimed to develop a nutritious instant purple sweet potato soup (PSP) combination with a variety of vegetables and freeze-dried chicken. The nutritional characteristics of the product were evaluated. The current study employs principal component analysis (PCA), consumer preference mapping, and check-all-that-apply (CATA) data processing to describe sensory instant mixed soup attributes. The results showed that the soup was made from the formula F2 (PSP flour 47.5%, orange-fleshed sweet potato flour 12.5%, potatoes 6%, banana 7%, mushroom 8%, petit poise 3%, pumpkin 5%, protein powder 5% and cream powder 6%) gave good quality, high sensory value and attractive colors product. The PCA identified important soup attributes such as sweetness, milk flavor, vegetable odor, and color. Adding 15% freeze-dried chicken improved the quality of mixed soup products with energy distribution from macronutrients: proteins 24%, carbohydrates 65%, and lipids 10%. The anthocyanin and β-carotene content analyzed from the product was 13.1 mg/100 g and 370.2 μg/100 g. Score analysis according to the CATA model with two main components accounting for 95.57% of the variance in sensory attribute data, showing liking attributes of mixed soup sample that the panelists preferred in color, flavor, chicken meat distribution, and sweetness. The essential nutritional characteristics of mixed soup have been carefully analyzed.
Keywords: Sweetness; Meat and Animal Product Quality